Astragalar anatomy of an early dinosaur from the Upper Triassic of southern Brazil. (3rd October 2021) - Müller, Rodrigo Temp
ABSTRACT: The morphology of the ankle is a crucial topic towards our understanding of the evolutionary history of Archosauria. The morphology of these bones is directly correlated with posture, and subsequently this provides an important phylogenetic signal. The astragalar anatomy is widely adopted in phylogenetic studies of dinosaurs, however, this bone is largely missing from some of our geologically oldest dinosaurian specimens. This is the case for Buriolestes schultzi, an early sauropodomorph from the Upper Triassic (Carnian) of southern Brazil. Here, a new astragalus is reported from the type locality of B. schultzi . The presence of a markedly rimmed and elliptical fossa posterior to the anterior ascending process corroborates saurischian affinities for this new specimen. Moreover, the short anteromedial corner of the element differs from that of several other post-Carnian sauropodomorphs. Additionally, the absence of the astragalar posterior crest in this specimen also differentiates it from several theropods. Unfortunately, there are no autapomorphic traits that support a reliable alpha taxonomic assignation. Therefore, the specimen in question cannot be positively assigned to B. schultzi . Conversely, there are no significant differences between the new specimen and B. schultzi, which could alternatively be supportive of a taxonomic assignment based on topotypical principles.